2019
DOI: 10.1089/neu.2018.6233
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Histological Gender Comparison of Age-Matched Rats after Moderate Thoracic Contusive Spinal Cord Injury

Abstract: Spinal cord injury (SCI) afflicts hundreds of thousands of Americans, and most SCI (*80%) occurs in males. In experimental animal models, however, many studies used females. Funding agencies like the National Institutes of Health recommend that new proposed studies should include both genders due to variations in gender response to injuries, diseases, and treatments. However, cost and considerations for some animal models, such as SCI, affect investigators in adapting to this recommendation. Research has incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
(50 reference statements)
1
19
0
Order By: Relevance
“…The extent to which sex influences outcomes following SCI remains controversial based on existing clinical and pre-clinical data. Several rodent studies have confirmed a female-biased protection on locomotor outcomes after SCI ( 14 17 ), while others have found no differences ( 18 , 19 ). Most prior work supporting sex-dependent effects after SCI have limited evaluations to locomotor outcomes and white matter sparing, which found marginal improvements favoring females.…”
Section: Resultsmentioning
confidence: 99%
“…The extent to which sex influences outcomes following SCI remains controversial based on existing clinical and pre-clinical data. Several rodent studies have confirmed a female-biased protection on locomotor outcomes after SCI ( 14 17 ), while others have found no differences ( 18 , 19 ). Most prior work supporting sex-dependent effects after SCI have limited evaluations to locomotor outcomes and white matter sparing, which found marginal improvements favoring females.…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence that the pathophysiology and recovery after SCI may be sex-dependent [13,14,[18][19][20][21][22][23]. This is especially true for neuropathic pain where sexdependent outcomes have been observed in both humans and rodents [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Only female nice were chosen because it is easier to express the bladders of female SCI mice and they have lower risk of complication ( Lilley et al, 2020 ). In addition, the study with only female mice are unlikely to cause experimental bias because the pathophysiology in male and female SCI animals appears to be similar ( Walker et al, 2019 ). The feasibility of the mouse model for this study is based on the facts that MNs in the mouse spinal cord are known to contain PICs ( Meehan et al, 2010 ), and spasms and enhanced spinal cord reflex have been well demonstrated in the SCI models with injury at T9-10 ( Skinner et al, 1996 ; Corleto et al, 2015 ; Tysseling et al, 2017 ; Mekhael et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%